Analysis of the Use of Circular Motion Physics Concepts on Game Rides in Jawa Timur Park 1 - Kirana Aureola Arzak; Shalsa Billa Ardhana Neswary; Hana Fitriyah (Indonesia Approach Education, 2021)
In general, physics has been widely spread well in everyday life, one of which is used as a concept in holiday destinations in Indonesia. In East Java, Jatim Park group has been established by a combination of education and entertainment, resulting in the concept of learning while playing. Jawa Timur Park 1 is one of the eduparks in Indonesia with the first playground in the East Java area, especially Batu City. This research aims to analyze the use of circular motion physics concepts on Sky Swinger, Superloop Coaster, Enterprise, Tornado and Pendulum 360 in Jawa Timur Park 1, Batu. Research is carried out using literature study methods by outlining the problems discussed clearly and in detail related to the concepts of physics contained in the game rides. The data collection method used in this study used review and observation journals. Observation is done using social media in the form of Youtube. In this study, it was concluded that in the Pendulum 360, Sky Swinger, Enterprise, Tornado, and Superloop Coaster Rides at Jatim Park 1 Batu there is a physical concept in the form of circular motion, and there is centripetal force, centrifugal force, and centripetal acceleration.